2017
DOI: 10.24200/sci.2017.4216
|View full text |Cite
|
Sign up to set email alerts
|

Efficient multi-objective optimization algorithms for construction site layout problem

Abstract: Abstract. Construction site layout planning is one of the managerial aspects of the construction industry and has significant impacts on performance of the sites. Since in real site layout optimization, many objectives are involved, therefore multi-objective algorithms are needed. In this study, multi-objective version of two meta-heuristics, CBO and ECBO, are developed and their applicability and performance are checked on a case study. The quality of the results obtained, verify the ability of these algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…In the selected articles, metaheuristic algorithms are widely used to solve the CSLP problems because of four major reasons: (1) considering combinatorial optimization problems, a global optimal solution is impossible (Ning et al , 2019; Said and El-Rayes, 2013a) or cannot be found at a reasonable cost (e.g. computational time) (Benjaoran and Peansupap, 2019; Farmakis and Chassiakos, 2018; Kaveh et al , 2018a; Razavialavi and Abourizk, 2017a; Li et al , 2015; Xu and Song, 2015; Kalmár et al , 2014); (2) more objectives and constraints should be considered for congested construction sites and large-scale projects (Kumar and Cheng, 2015; Kaveh et al , 2018b; Abdelmegid et al , 2015; Xu and Li, 2012; Said and El-Rayes, 2011); (3) the metaheuristic algorithms are not problem-specific (Li et al , 2019; Khalafallah and Hyari, 2018), and the derivatives of objective functions are not required (Kaveh and Vazirinia, 2019; Xu et al , 2016b; Gholizadeh et al , 2010; Zhou et al , 2009); and (4) in complex mathematical models (e.g. bi-level models), it is difficult to use exact algorithms to find all feasible solutions (Song et al , 2016, 2018a; Li et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the selected articles, metaheuristic algorithms are widely used to solve the CSLP problems because of four major reasons: (1) considering combinatorial optimization problems, a global optimal solution is impossible (Ning et al , 2019; Said and El-Rayes, 2013a) or cannot be found at a reasonable cost (e.g. computational time) (Benjaoran and Peansupap, 2019; Farmakis and Chassiakos, 2018; Kaveh et al , 2018a; Razavialavi and Abourizk, 2017a; Li et al , 2015; Xu and Song, 2015; Kalmár et al , 2014); (2) more objectives and constraints should be considered for congested construction sites and large-scale projects (Kumar and Cheng, 2015; Kaveh et al , 2018b; Abdelmegid et al , 2015; Xu and Li, 2012; Said and El-Rayes, 2011); (3) the metaheuristic algorithms are not problem-specific (Li et al , 2019; Khalafallah and Hyari, 2018), and the derivatives of objective functions are not required (Kaveh and Vazirinia, 2019; Xu et al , 2016b; Gholizadeh et al , 2010; Zhou et al , 2009); and (4) in complex mathematical models (e.g. bi-level models), it is difficult to use exact algorithms to find all feasible solutions (Song et al , 2016, 2018a; Li et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Collisions between bodies occur based on two laws of physics; the laws of conservation of momentum and energy. These two laws are conserved in an isolated system, while the collision is taking place [27]. This algorithm, by imitating this phenomenon, provides a method for solving complex optimization problems.…”
Section: Enhanced Non-dominated Sorting Colliding Bodies Optimizationmentioning
confidence: 99%
“…Like other population based algorithms, the multi-objective version of the ECBO, ENSCBO, developed by Kaveh et al [27], starts with a population of random colliding bodies (CB). Each CB is known as a solution candidate and has a specific mass.…”
Section: The Enscbo Algorithm Mechanismmentioning
confidence: 99%
“…Another important point for the implementation of all industrial and construction projects is the safety level and factors affecting it. This is a vital issue because endangered safety of workers, managers and equipment may lead to costly postponements and heavy private or public fines when workers' safety is at risk (Kaveh et al, 2018). Therefore, a suitable model should be proposed for proper facilities layout in construction projects efficiently by considering all of the effective factors.…”
Section: Introductionmentioning
confidence: 99%